The Plasma [Kynurenine]/[Tryptophan] Ratio and Indoleamine 2, 3-Dioxygenase: Time for Appraisal. (August 2019) - Badawy, Abdulla A-B; Guillemin, Gilles
The plasma kynurenine to tryptophan ([Kyn]/[Trp]) ratio is frequently used to express or reflect the activity of the extrahepatic Trp-degrading enzyme indoleamine 2, 3-dioxygenase (IDO). This ratio is increasingly used instead of measurement of IDO activity, which is often low or undetectable in immune and other cells under basal conditions, but is greatly enhanced after immune activation. The use of this ratio is valid in in vitro studies, eg, in cell cultures or isolated organs, but its 'blanket' use in in vivo situations is not, because of modulating factors, such as supply of nutrients; the presence of multiple cell types; complex structural and functional tissue arrangements; the extracellular matrix; and hormonal, cytokine, and paracrine interactions. Determinants other than IDO may therefore be involved in vivo. These are hepatic tryptophan 2, 3-dioxygenase (TDO) activity and the flux of plasma-free Trp down the Kyn pathway. In addition, conditions leading to accumulation of Kyn, eg, inhibition of activities of Kyn monooxygenase and kynureninase, could lead to elevation of the aforementioned ratio. In this review, the origin of use of this ratio will be discussed, variations in extent of its elevation will be described, evidence against its indiscriminate use will be presented, and examining determinants other than IDO activity and their correlates will be proposed for future studies.